Smooth Muscle Hypocontractility and Airway Normoresponsiveness in a Mouse Model of Pulmonary Allergic Inflammation - Boucher, Magali; Henry, Cyndi; Dufour-Mailhot, Alexis; Khadangi, Fatemeh; Bossé, Ynuk (Frontiers in Physiology, 2021)
The contractility of airway smooth muscle (ASM) is labile. Although this feature can greatly modulate the degree of airway responsiveness in vivo, the extent by which ASM’s contractility is affected by pulmonary allergic inflammation has never been compared between strains of mice exhibiting a different susceptibility to develop airway hyperresponsiveness (AHR). Herein, female C57BL/6 and BALB/c mice were treated intranasally with either saline or house dust mite (HDM) once daily for 10 consecutive days to induce pulmonary allergic inflammation. The doses of HDM were twice greater in the less susceptible C57BL/6 strain. All outcomes, including ASM contractility, were measured 24 h after the last HDM exposure. As expected, while BALB/c mice exposed to HDM became hyperresponsive to a nebulized challenge with methacholine in vivo, C57BL/6 mice remained normoresponsive. The lack of AHR in C57BL/6 mice occurred despite exhibiting more than twice as much inflammation than BALB/c mice in bronchoalveolar lavages, as well as similar degrees of inflammatory cell infiltrates within the lung tissue, goblet cell hyperplasia and thickening of the epithelium. There was no enlargement of ASM caused by HDM exposure in either strain. Unexpectedly, however, excised tracheas derived from C57BL/6 mice exposed to HDM demonstrated a decreased contractility in response to both methacholine and potassium chloride, while tracheas from BALB/c mice remained normocontractile following HDM exposure. These results suggest that the lack of AHR in C57BL/6 mice, at least in an acute model of HDM-induced pulmonary allergic inflammation, is due to an acquired ASM hypocontractility.